Removal of perennial herbaceous species affects response of Cold Desert shrublands to fire - Chambers, Jeanne C.; Board, David I.; Roundy, Bruce A.; Weisberg, Peter J. (Journal of vegetation science, 2017)
Questions: Two of the primary global change factors that threaten shrublands worldwide are loss of native perennial herbaceous species due to inappropriate livestock grazing and loss of native shrubs due to altered fire regimes. We asked: (1) how do the separate and interacting effects of removal of perennial herbaceous species and burning influence relative abundance of plant functional groups over longer time frames; and (2) how do interactions between perennial herbaceous species removal and burning differ along environmental gradients? We discuss implications of our findings for ecosystem resilience to these disturbances. Location: Shoshone Mountain Range, Nevada and East Tintic Range, Utah, USA. Methods: We used a factorial experiment to test effects of perennial herbaceous species removal (0%, 50% and 100%) and burning (burned and not burned) on plant functional group cover along elevation gradients within watersheds characterized by Artemisia tridentata Nutt. vegetation types. The experiment was conducted in two locations (Nevada and Utah) with sites located at low (1960 and 1710 m), mid (2190 and 2085 m) and high (2380 and 2274 m) elevations and was repeated in 2 yr. Percentage cover of native and exotic species and canopy area, density and size of the shrub A. tridentata were evaluated 12 and 13 yrafter study implementation. Results: Over a decade later, removal treatments resulted in highly significant decreases (40–62%) in perennial native grass and forb cover across site elevations. Burning decreased overall shrub and A. tridentata cover, but effects on perennial native grass cover differed among elevations. Removal had strong positive effects on A. tridentata seedling recruitment and resulted in progressive increases in density and canopy area following burning. A. tridentata canopy areas on burned plots with 0%, 50% and 100% removal were 0.19, 0.40 and 0.84 m2, respectively. Annual invasive grass density also increased with degree of removal, and both density and cover decreased with elevation. Conclusions: Our results show that loss of perennial herbaceous species, which can result from inappropriate livestock grazing, and loss of shrubs, which often results from fire, interact to affect key functional groups. The implications are that ecosystem resilience to disturbance in Cold Desert shrublands decreases when competition from perennial native grasses and forbs for available resources no longer prevents dominance by A. tridentata and other shrubs and/or annual invasive grasses. Managing livestock grazing to maintain or increase perennial herbaceous species, especially deep-rooted grasses, which contribute to resilience along elevation gradients, can help prevent threshold crossings to undesirable states and retain critical ecosystem services following disturbances such as wildfire.